Indole-3-carbinol regulates microglia homeostasis and protects the retina from degeneration - Khan, Amir Saeed (J Neuroinflammation, 2020)
BACKGROUND: Retinal degenerative diseases significantly contribute to visual impairment and blindness. Microglia reactivity is a hallmark of neurodegenerative diseases including retinal cell death and immunomodulation emerges as a therapeutic option. Indole-3-carbinol (I3C) is a natural ligand of aryl hydrocarbon receptor (AhR), with potent immunomodulatory properties. Here, we hypothesized that I3C may inhibit microglia reactivity and exert neuroprotective effects in the light-damaged murine retina mimicking important immunological aspects of retinal degeneration. METHODS: BV-2 microglia were treated in vitro with I3C followed by lipopolysaccharide (LPS) stimulation to analyze pro-inflammatory and anti-oxidant responses by quantitative real-time PCR (qRT-PCR) and Western blots. Nitric oxide (NO) secretion, caspase 3/7 levels, phagocytosis rates, migration, and morphology were analyzed in control and AhR knockdown cells. I3C or vehicle was systemically applied to light-treated BALB/cJ mice as an experimental model of retinal degeneration. Pro-inflammatory and anti-oxidant responses in the retina were examined by qRT-PCR, ELISA, and Western blots. Immunohistochemical staining of retinal flat mounts and cryosections were performed. The retinal thickness and structure were evaluated by in vivo imaging using spectral domain-optical coherence tomography (SD-OCT). RESULTS: The in vitro data showed that I3C potently diminished LPS-induced pro-inflammatory gene expression of I-NOS, IL-1ß, NLRP3, IL-6, and CCL2 and induced anti-oxidants gene levels of NQO1, HMOX1, and CAT1 in BV-2 cells. I3C also reduced LPS-induced NO secretion, phagocytosis, and migration as important functional microglia parameters. siRNA-mediated knockdown of AhR partially prevented the previously observed gene regulatory events. The in vivo experiments revealed that I3C treatment diminished light-damage induced I-NOS, IL-1ß, NLRP3, IL-6, and CCL2 transcripts and also reduced CCL2, I-NOS, IL-1ß, p-NFkBp65 protein levels in mice. Moreover, I3C increased anti-oxidant NQO1 and HMOX1 protein levels in light-exposed retinas. Finally, I3C therapy prevented the accumulation of amoeboid microglia in the subretinal space and protected from retinal degeneration. CONCLUSIONS: The AhR ligand I3C potently counter-acts microgliosis and light-induced retinal damage, highlighting a potential treatment concept for retinal degeneration.